"Pharmacy counselling": a study of the pharmacist/patient encounter using conversation analysis - Pilnick, Alison (1997)
Pharmacy as a profession is changing rapidly in the UK. Over recent years, the increased utilization of ready-prepared drugs has led to a decline in the need for the traditional skills of formulation, while computerization has resulted in a situation where much of the routine dispensing work can be undertaken by less qualified personnel. The decline in the traditional aspects of pharmacy has been matched by the emergence of a much greater advisory role. Pharmacy practice researchers have been drawn to support these developments by investigating related areas, but the common factor linking this research is its focus on clinical as opposed to communication issues. Rather than investigating the nature of face-to-face interaction between pharmacists and clients as a topic in itself, researchers instead have been largely concerned with patient/health care system mteractions as a function of drug therapy. Those few studies that have focused exclusively on communication have done so from a quantitative, social psychology framework, thus ignoring the two way, reactive nature of the interaction process.